(untitled) (Bucharest Working Papers in Linguistics, 2024)
The current study investigates experimentally whether the General Adjective Hierarchy Size > Age > Shape > Color holds for British English and Romanian native speakers alike, and whether Romanian exhibits a mirror order of English, as argued in Cinque (1994, 2005, 2010) or whether Romanian exhibits a more flexible ordering than English (Cornilescu & Nicolae 2016, Cornilescu & Cosma 2019, Leivada & Westergaard 2019). The results from a forced choice task conducted both in British English and Romanian support the idea that English observes the fixed hierarchy Size > Age > Shape > Color overall, while Romanian is more flexible in its ordering. These results go against Cinque’s (1994) cartographic theory that Romance is a mirror of English, as well as against Scontras et al.’s (2017) theory of subjectivity; instead, the results may be captured by free adjunction. Our findings for English and Romanian support the idea that certain languages (like English) observe general hierarchies for adjectives, while other languages (like Romanian) do not.